Answer:
So starting off with 1a f(4)
We simply substitute x with 4 for the function
f(4)=2(4)-5
f(4)=8-5
f(4)=3
Next 1b, here it's a little different since you have to multiply the functions I think ( please correct me if I'm wrong).
gf(4), basically means functions g and f are being multiplied and their variables are being substituted with 4.
g(4)=4^2+3
g(4)=16+3
g(4)=19
and we also know from before that f(4)=3, so we'll do 19 times 3 which is 57
For the next two, I may be wrong, but I'm still going to try:
anything to the power of a negative is a fraction so for f^-1(x)=2x-5 we'll have 1/f(x)=x/2+5/2
And then for g^-1, we'll have 1/g(x)=
![√(x-3) √(x-3)](https://img.qammunity.org/2022/formulas/mathematics/high-school/rwcd3ehnl6itzohks8hva7fg0ds6na0i9o.png)
Hope I helped :)